Heating, cooling, lighting : design methods for architecs - Lechner, Norbert (New York : John Wiley and Sons, 1991)
This book is about: heating, Cooling; and Lighting as form-givers in architecture...
Keywords: Heating; Ventilation; Air conditioning; Heating; Air conditioning; Lighting; Architectural design -- Environmental aspects